Nutritional Composition, Toxicity Study Of Squid And Cuttlefish Ink Hydrolysates And Flavour Improvement Using Maillard Reaction - Zulkipli, Ayu Shazwani (2021)
The objectives of this study were to investigate the nutritional composition, acute oral toxicity and flavour improvement of squid ink enzyme hydrolysates powder (SIEHP) and cuttlefish ink enzyme hydrolysates powder (CIEHP). SIEHP was hydrolysed by Alcalase® at pH 8 and 55°C, while CIEHP was hydrolysed by papain at pH 6 and 55°C for 4 h and 3% (w/v) enzyme-substrate ratio, respectively. Proximate composition and trace metals analysis was conducted. Toxicity study on animals was performed according to Organization for Economic Co-operation and Development (OECD) No. 425. One group served as control and two treated groups received 2000 mg/kg b.w (limit test) of SIEHP and CIEHP at a single dose orally. All groups were observed for 14 days and the organs of euthanized rats were preserved for histopathological examination. The SIEHP and CIEHP were heated with D-xylose and L-cysteine or D-xylose at 120°C, pH 7.4 for 2 h and labelled as SIEHP-mx or SIEHP-x, CIEHP-mx or CIEHP-x to explored characteristics of Maillard reaction. The sensory profile was assessed based on quantitative descriptive analysis (QDA) by 10 trained panellists, while the sensory acceptability was performed on 30 consumers towards appearance, odour, flavour, aftertaste and overall acceptability. The findings revealed SIEHP and CIEHP had higher protein and ash content but lower fat and moisture content than ink without hydrolysis